Rites of justice : the sacraments and liturgy as ethical imperatives - McKenna, Megan (Maryknoll, N.Y. : Orbis Books, 1997)
"Megan McKenna leads us to look closely at our prized possessions: the rituals of the church that protect our world from the ravages of evil and injustice and keep alive our hopes for love and goodness. In her engaging, unique style, McKenna combines the study of scripture and church teachings with storytelling as she walks us through the Rites of Initiation, Baptism, Eucharist, Confirmation, Reconciliation, Anointing of the Sick, Marriage, and Orders. Her reflections show how the rituals of the church inextricably connect us to the ethics of Jesus." "Rites of Justice explores each sacrament fully, including its origins in scripture, its practice today, its ethical teaching, and what this means for the way we live our lives. Throughout there is constant reference to the Rite for Christian Initiation of Adults, including an extended ritual written by McKenna intended for use with the majority of Christians, baptized as infants, who never received formal initiation as adults into the rituals of the church."
The liturgy : do justice in word and bread.
Includes bibliographical references (p. 238-244)
Keywords: Sacraments -- Catholic Church; Catholic Church -- Liturgy; Catholic Church -- Doctrines